2001
DOI: 10.1097/00001756-200103260-00049
|View full text |Cite
|
Sign up to set email alerts
|

Quinolinic acid induces oxidative stress in rat brain synaptosomes

Abstract: The oxidative action of quinolinic acid (QUIN), and the protective effects of glutathione (GSH), and 2-amino-5-phosphonovaleric acid (APV), were tested in rat brain synaptosomes, Reactive oxygen species (ROS) formation was quantified after the exposure of synaptosomes to increasing concentrations of QUIN (25-500 microM). The potency of QUIN to induce lipid peroxidation (LP) was tested as a regional index of thiobarbituric acid-reactive substances (TBARS) production, and the antioxidant actions of both GSH (50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
98
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(101 citation statements)
references
References 23 publications
2
98
0
Order By: Relevance
“…That is, unless such action of QUIN can be causally linked to an additional process such as lipid peroxidation that has a definite potential to compromise the capillary barrier. 19 The results of the present study strongly imply that QUIN can, indeed, cause lipid peroxidation in brain microvessels. There could be regional variations in the exact mechanism of the action of QUIN: in comparison to hippocampus and the entorhinal cortex, the lipid peroxidation in the striatum was less sensitive to the NMDA-R antagonist D-2-APV, possibly suggesting the presence of an NMDA-R independent component of the mechanism (Table 1; see Pláteník et al 20 for an example of such mechanism).…”
Section: Discussionsupporting
confidence: 69%
“…That is, unless such action of QUIN can be causally linked to an additional process such as lipid peroxidation that has a definite potential to compromise the capillary barrier. 19 The results of the present study strongly imply that QUIN can, indeed, cause lipid peroxidation in brain microvessels. There could be regional variations in the exact mechanism of the action of QUIN: in comparison to hippocampus and the entorhinal cortex, the lipid peroxidation in the striatum was less sensitive to the NMDA-R antagonist D-2-APV, possibly suggesting the presence of an NMDA-R independent component of the mechanism (Table 1; see Pláteník et al 20 for an example of such mechanism).…”
Section: Discussionsupporting
confidence: 69%
“…Some studies have demonstrated the neurotoxicity of KYN and its metabolite QA by stimulating NMDA receptor. 40,41) However, KYNA, another metabolite of KYN, is known as an antagonist of the NMDA receptor and can reduce NMDA overstimulation to protect neurons. 42) This imbalance between neurotoxic and neuroprotective metabolites may result in a greater neurotoxic damage through NMDA receptor.…”
Section: Discussionmentioning
confidence: 99%
“…The TDO2 enzyme plays a role in the transformation of the tryptophan to kynurenine [57] and increased concentrations of kynurenine metabolics leads to neurotoxic effects [52].…”
Section: Discussionmentioning
confidence: 99%